PELAKSANAAN KEBIJAKAN BANTUAN OPERASIONAL KESEHATAN DI KABUPATEN OGAN ILIR, SUMATERA SELATAN - Ainy, Asmaripa (Jurnal Kebijakan Kesehatan Indonesia, 2012)
ABSTRACTIntroduction: The Ministry of Health of Indonesia Republichas issued a policy on health operational fund (BOK) to increasethe access of service in health centers based on a decree ofthe Minister of Health Number 494/Menkes/SK/IV/2010 updatedthrough the regulation of the Minister of Health Number 210/Menkes/Per/I/2011 dated 31st January 2011 on the technicalguidelines for BOK. Ogan Ilir District has supported that policythrough a decree issued by the head of health office Number440/337/DKES/III/2011 and 440/22/DKES/III/2011, which eachregulates the forming of the management of Jamkesmas,Jampersal, and BOK as well as budget managers. This studyaimed to analyze the implementation of BOK policy in Ogan IlirDistrict.Methods: This study was an analysis of policy. The primarydata were obtained through direct observation and in-depthinterviews to 4 informants: Head of Ogan Ilir Health Office,management staff at Ogan Ilir Health Office, Head of IndralayaHealth Center and management staff at Indralaya Health Center.The secondary data were obtained through review of BOKdocuments.Results: BOK in Ogan Ilir had been implemented in 2010 throughthe social assistance and in April 2011 by co-administration bythe health office. The organizing of BOK referred to thetechnical guideline from the Ministry of Health. Financialmanagement referred to the financial management guidelinefrom the Directorate General of Nutrition and Maternal andChild Health. Disbursement of BOK began from proposing Planof Actions (POA) from health centers to health office to verifythe funds and then proposing disbursement to KPPN. The fundfor implementing program could be taken from BOK treasurer.The allocation of BOK at health centers was adjusted for thenumber of working areas, population, program coverage andgeographical conditions. BOK was prioritized for healthpromotion such as: maternal and child health, nutrition, bodymass index measurement, and communicable diseases. PerApril-June 2011, the fund for secretariat had been disbursedabout 40% used for dissemination, training and transport forhealth center treasurer. Reporting of BOK conducted fromhealth center to health office was on every date 5 thenforwarded to the province and to the Ministry of Health everymonth via online, as well as a written report to KPPN.Conclusion: The implementation of BOK in Ogan Ilir referredto the policy of the Ministry of Health and was followed upwith the policy of district health office. POA proposal is decisivedin the disbursement of BOK so it is recommended to the headof Ogan Ilir District Health Office to routinely ensuredissemination about BOK and guide all health centers inpreparation of POA for implementing policy effectively.Keywords: financing policy, health operational fund, healthcenter